Laparoscopic approach of the mare as an aid in reproductive assisted technology - Fialho, Sergio da Silva (2001)
Laparoscopy is a poorly explored tool for equine assisted reproduction techniques, despite its use in man, zoo and domestic animals. This study had the objective to evaluate the possibility and offer basis for cannulation of the oviduct and its future application in gamete and embryo transfer programs in this species. Seventeen standing laparoscopies were accomplished in ten mares, each ovary approached from its ipsolateral flank. After identification of the uterine tube, the infundibulum was gently tractioned and a catheter advanced in direction of the abdominal ostium of the uterine tube to the ampulla where 250 µL of culture medium (Dulbecco's - PBS) were deposited. The laparoscopic technique associated with assisted reproduction in the mare can be considered pioneer and have the potential of lowering costs with maintenance of receptors by taking advantage of repetitive cycles, which is impossible by means of the conventional approach through laparotomy. This cost is one of the main obstacles for the commercial application of assisted reproduction techniques in horses.